RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG TANAH (arachis hypogaea L.)TERHADAP PEMBERIAN MACAM MULSA DAN BIOURINE - Istiqomah Istiqomah; Fernanda Kurniawan; Choirul Anam (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
Groundnut (Arachis hypogaea L.) is a crop that produces agricultural products. As it allows for effective agro-industrial development to support the local economy, groundnut is highly influential as a source of income for farmers. Soils that contain many chemicals may be the cause of low groundnut production in Indonesia. The objective of this study was to determine the types of mulch and biourine that affect the growth and production of groundnut plants. This study was conducted in kadutan hamlet, mlangi village, widang sub-district, tuban district, from april to july 2022. Factorial Randomized Group Design (RAK) method was used in this study. The RAK consisted of two factors: the first factor determined the type of mulch: no mulch, straw mulch, and sawdust mulch; and the second factor determined the type of biourine: no biourine, rabbit biourine, and cow biourine. Plant height, number of leaves, number of pods per sample and per plot, pod weight per sample, and wet stover weight per plot were all observed parameters. Data were calculated using fisher's analysis of variance (F test at 5% level). The combination treatment of sawdust mulch and rabbit biourine proved to have a positive impact on growth and production. If there was a significant difference, the BNT (Least significant difference) test was applied.